A review of liquid-liquid flow patterns in horizontal and slightly inclined pipes - Ibarra,R; Markides,CN; Matar,OK (Multiphase Science and Technology, 2014)
© 2014 by Begell House, Inc. This paper presents a review of the co-current flow of two immiscible liquids in horizontal and slightly inclined pipes. Liquid-liquid flows are present in a wide variety of industrial processes, such as chemicals, pharmaceuticals, and food processing. However, this phenomenon is mainly studied in the oil industry, especially in the analysis of oil-water mixtures encountered in long transportation pipelines from the wellhead to the processing facility. The hydrodynamic behavior of liquid-liquid flows is more complex than that of gas-liquid flows because of density ratio, viscosity ratio, interfacial forces, and pipe wettability. This means that a significant number of different flow patterns can be obtained from different fluid properties and pipe characteristics. Furthermore, the flow pattern classification of liquid-liquid flows is arbitrary and several researchers use their own classification, complicating comparison and analysis of flow pattern maps. In this paper, a unified flow pattern classification for liquid-liquid flow is proposed. This classification enables the direct comparison of flow pattern maps for further analysis.